Strategy Analysis of the 2022 Winter Olympics in Hebei Province - Hui, Dong; Zhong, Huamei (Advances in Social Sciences Research Journal, 2016)
Based on the research situation analysis of preparations for the current large-scale sport events by the method of literature review and according to the actual situation of Hebei Province, this article analyzes the challenges and opportunities brought by the 2022 Winter Olympics to Hebei Province and puts forward proposals for the  preparations. In the run-up to the 2022 Winter Olympics, the biggest challenge to Hebei Province will be traffic, sports science and technology service and the lack of experience on preparations and management for sport event. The holding of Winter Olympics will facilitate industrial transformation and upgrade and boost the economic development and cultural transmission of Heibei Province. Positive strategy shall be adopted during the preparation period of 2022 Winter Olympics and cooperation between the governments of Beijing and Hebei Province shall be strengthened. Hebei Province shall implement the talent introduction strategy, strengthen infrastructure construction and establish sport event schedule, management system, evaluation mechanism and security assurance system